A Theoretical and Statistical Analysis of the Determinants of the Currency-Demand Deposit Ratio for the United States, 1952 to 1971 - Becker, William E. (Journal of Finance, 1975)
William E. Becker, Jr., A Theoretical and Statistical Analysis of the Determinants of the Currency-Demand Deposit Ratio for the United States, 1952 to 1971, The Journal of Finance, Vol. 30, No. 4 (Sep., 1975), p. 1144